Aspek Hukum Pengaturan Penyertaan Modal Negara Kepada Lembaga Keuangan Internasional - Mahesa, Agni (Fakultas Hukum Universitas Islam Jakarta, 2016)
long with the government's involvement in membership of International Financial Institutions, the Government is required to contribute in accordance with the article of agreement of the establishment of the International Financial Institution. Contribution given to Lemhaga Finance International is done in the form of state capital participation. The problem faced is the participation of state capital from the side of state finance financing is always associated with the issuance of Government Regulation as a legal instrument of separation of state assets. However, none of the specific and specific regulatory or regulatory regulations concerning the implementation of state equity participation to the International Financial Institution includes the need for the issuance of a Government Regulation. This certainly led to confusion in the implementation of state capital participation to the International Financial Institutions. Who are the competent authorities, what legal instruments are required in the participation of state capital to the International Financial Institution is a matter that must be studied for orderly administration of state finance. Implementation of state equity participation must also be done with a mandate, because the given capital is the mandate of the Government entrusted to be managed properly in order to achieve the goal of the creation of people's welfare state. ABSTRAK Seiring dengan keterlibatan pemerintah dalam keanggotaan Lembaga Keuangan Internasional, Pemerintah dituntut untuk memberikan kontribusi sesuai dengan article of agreement pembentukan Lembaga Keuangan Internasional tersebut. Kontribusi yang diberikan kepada Lemabaga Keuangan Internasional tersebut dilakukan dalam bentuk penyertaan modal negara. Permasalahan yang dihadapi adalah penyertaan modal negara dari sisi pembiayaan keuangan negara selalu dikaitkan dengan penerbitan Peraturan Pemerintah sebagai instrumen hukum pemisahan kekayaan negara. Namun demikian, tidak ada satupun peraturan perundang-undangan (regeling) yang mengatur secara khusus dan spesifik mengenai pelaksanaan penyertaan modal negara kepada Lembaga Keuangan Internasional termasuk perlunya penerbitan Peraturan Pemerintah. Hal ini tentu mengakibatkan kebingungan dalam pelaksanaan penyertaan modal negara kepada Lembaga Keuangan Internasional. Siapa pihak yang berwenang, instrumen hukum apa yang diperlukan dalam penyertaan modal negara kepada Lembaga Keuangan Internasional merupakan hal yang harus dikaji demi tertibnya administrasi keuangan negara. Pelaksanaan penyertaan modal negara juga harus dilakukan dengan amanah, karena modal yang diberikan merupakan amanah Pemerintah yang dititipkan untuk dikelola dengan benar guna mencapai tujuan negara yaitu terciptanya kesejahteraan rakyat.